N-acetylcysteine prevents cadmium-induced apoptosis in human breast cancer MDA-MB468 cell line - Panjehpour, M.; Alaie, H. (Cellular and Molecular Biology, 2014)
Cadmium is a heavy metal posing severe risks and destructive effects on human health. Although cadmium was classified as a human carcinogen, it has been also shown to be a cytotoxic agent that induces cell death either by necrosis or apoptosis. In this study, we investigated the protective role of N-acetylcysteine, a free radical scavenger, on cadmium induced apoptosis in MDA-MB468 cells. The breast cancer cells were exposed to increasing concentrations of CdCl2 in the presence and absence of NAC and the cell viability was assessed using MTT assay. The microscopic studies of apoptosis were carried out with fluorescent staining. To investigate the induction of apoptosis, cellular DNA was isolated using DNA kit extraction and analyzed electrophoretically. The results showed significant decrease in cellular viability upon 48 hours exposure to CdCl2 in a dose-dependent manner (p < 0.05). Pretreatment of MDA-MB468 cells with N-acetylcysteine (1mM) reversed the cadmium cytotoxicity effects and protected cells from apoptotic death. DNA Hoechst staining showed the apoptotic bodies. The electrophoresis of extracted DNA identified a fragmentation pattern consistent with apoptosis mechanism. The results suggest that cytotoxic effects and induction of apoptosis caused by CdCl2 are mediated, by oxidative stress.